1996
DOI: 10.1101/gad.10.24.3156
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human lysosomal neuraminidase defines the molecular basis of the metabolic storage disorder sialidosis.

Abstract: Neuraminidases (sialidases) have an essential role in the removal of terminal sialic acid residues from sialoglycoconjugates and are distributed widely in nature. The human lysosomal enzyme occurs in complex with 13-galactosidase and protective protein/cathepsin A (PPCA), and is deficient in two genetic disorders: sialidosis, caused by a structural defect in the neuraminidase gene, and galactosialidosis, in which the loss of neuraminidase activity is secondary to a deficiency of PPCA. We identified a full-leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
243
1
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(257 citation statements)
references
References 73 publications
5
243
1
8
Order By: Relevance
“…Patients homozygous for c.625delG and c.4 _ 7dupACTG mutations belong to a severe infantile-onset form of sialidosis associated with dysostosis multiplex, dysmorphic phenotype, hepatosplenomegaly, and ascites [Pshezhetsky et al, 1997;Lukong et al, 2000]. Another deletion, c.1209delC [Bonten et al, 1996], caused a frameshift that extended the sialidase protein by 69 amino acids. Transient expression of the mutant protein showed that it does not have enzymatic activity and is not transported to the lysosome [Bonten et al, 1996].…”
Section: Insertions and Deletionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients homozygous for c.625delG and c.4 _ 7dupACTG mutations belong to a severe infantile-onset form of sialidosis associated with dysostosis multiplex, dysmorphic phenotype, hepatosplenomegaly, and ascites [Pshezhetsky et al, 1997;Lukong et al, 2000]. Another deletion, c.1209delC [Bonten et al, 1996], caused a frameshift that extended the sialidase protein by 69 amino acids. Transient expression of the mutant protein showed that it does not have enzymatic activity and is not transported to the lysosome [Bonten et al, 1996].…”
Section: Insertions and Deletionsmentioning
confidence: 99%
“…Another deletion, c.1209delC [Bonten et al, 1996], caused a frameshift that extended the sialidase protein by 69 amino acids. Transient expression of the mutant protein showed that it does not have enzymatic activity and is not transported to the lysosome [Bonten et al, 1996]. Duplication c.1193 _ 1198dupACCACT [Bonten et al, 2000] caused an in-frame duplication of H399 and Y400 amino acid residues and produced a mutant protein with about 30% of residual activity.…”
Section: Insertions and Deletionsmentioning
confidence: 99%
See 3 more Smart Citations